The Development of the Tourism Sector in Improving the Regional Economic Growth of Mojokerto Regency - Muhammad Ridwan Basalamah; M. Cholid Mawardi (Manunggal Halim Jaya, 2022)
Tourism is one sector that is being seriously worked on by countries in the world to encourage the national economy. The purpose of this research is how to implement strategy development to increase regional economic growth and what are the positive implications of implementing strategy development to increase regional economic growth in Mojokerto Regency, East Java, Indonesia. Research and methods in this study used qualitative method with the analysis of the interaction patterns used Miles and Huberman of Data Collection, Data Reduction, Data Presentation and Conclusions and Verification. The results of this study show governance in the development of tourism-based village potential in Mojokerto Regency, especially Ketapanrame Village, is one proof where the village government can invite the community to work together to realize a common goals. From this it can be state that village officials or village heads are able to give trust to the community where not all leaders can do this. With the existence of several tours such as the Ganjaran park and Sumber Gempong, the Trawas Village Head admits that the community's economic level is slowly getting better. Managing village potential is not only temporary if the development process but also the utilization after that.